2000
DOI: 10.1192/bjp.176.6.531
|View full text |Cite
|
Sign up to set email alerts
|

Labour and delivery complications and schizophrenia

Abstract: Other than among young-onset males we found no increase in labour and delivery complications among cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The women with affective psychoses were subdivided into a unipolar depression group (N=686, ICD-9 codes 296.1, 296.6, 296.8, and 296.9) and a bipolar disorder group (N=763, ICD-9 codes 296.0 and 296. [2][3][4][5]. The cohort had a JABLENSKY, MORGAN, ZUBRICK, ET AL.…”
Section: Case Definition and Diagnosesmentioning
confidence: 95%
See 1 more Smart Citation
“…The women with affective psychoses were subdivided into a unipolar depression group (N=686, ICD-9 codes 296.1, 296.6, 296.8, and 296.9) and a bipolar disorder group (N=763, ICD-9 codes 296.0 and 296. [2][3][4][5]. The cohort had a JABLENSKY, MORGAN, ZUBRICK, ET AL.…”
Section: Case Definition and Diagnosesmentioning
confidence: 95%
“…Mat ernal obstetric complications are widely regarded as environmental contributors to schizophrenia risk, although the evidence is still inconclusive. While metaanalyses of a number of case-control studies (1)(2)(3) suggest that significant associations exist between adult schizophrenia and exposure to obstetric complications, several population-based investigations (4)(5)(6) have failed to demonstrate excess occurrence of obstetric complications in individuals who developed schizophrenia compared to those who did not. The sources of discrepant findings are likely to include different definitions of obstetric complications, the use of retrospective maternal recall versus prospectively collected obstetric data, differences between rating scales, and variation in sample size and selection.…”
mentioning
confidence: 97%
“…Some studies have documented an increased frequency of obstetric complications in pregnancies of males with schizophrenia (Byrne et al, 2000; Dalman et al, 1999; Hultman et al, 1999; O'Callaghan et al, 1992; Preti et al, 2000), others have documented an increased frequency of obstetric complications in pregnancies of females with schizophrenia (Verdoux and Bourgeois, 1993), and still other studies have concluded that there is no difference in rates of obstetric complications by sex of affected individuals (Byrne et al, 2007; Geddes et al, 1999; Verdoux et al, 1997). However, when we draw our attention to specific obstetric complications, such as Rhesus D incompatibility, there is evidence to suggest that there may be sex-specific differences related to risk for schizophrenia (Byrne et al, 2000; Hollister et al, 1996; Insel et al, 2005) and that is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…There have been eight studies (Byrne et al, 2000; Hollister and Kohler, 2001; Hollister et al, 1996; Insel et al, 2005; Kendell et al, 2000; Kraft et al, 2004; Palmer et al, 2002; Sacker et al, 1995) and 2 meta-analyses (Cannon et al, 2002; Geddes et al, 1999) to directly or indirectly examine Rhesus D incompatibility as a risk factor for schizophrenia (briefly summarized in Table 1). The indirect studies tend to represent the earlier studies of Rhesus D incompatibility and schizophrenia, and are based on maternal recall or information from labor and birth records ascertained retrospectively or prospectively.…”
Section: Introductionmentioning
confidence: 99%
“…The association between obstetric complications and schizophrenia has been widely cited as crucial support for developmental and etiologic models of the disorder, although at least two population-based studies have failed to identify any associations [11,12]. Cannon et al [13] reviewed the literature on obstetric complications as risk factors for schizophrenia.…”
Section: Adverse Events During Pregnancy and Deliverymentioning
confidence: 98%